Vers une vulgarisation participative. Étude de cas : le Zaïre - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
À l'heure où les services de vulgarisation font l'objet de critiques quant